ANALISIS MANAJEMEN SYARIAH PEMANFAATAN PROGRAM DANA DESA UNTUK PEMBANGUNAN DESA DI MASA PANDEMI COVID-19 - Risnawati; Thantawi, Tubagus Rifqy; Mubarok, Mohamad Kharis (Jurnal Penelitian Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2023)
Pasarean Village is a village located in Pamijahan District, Bogor Regency. A common problem that occurs is the reallocation of the use of the Village Fund in 2020 causing many activities or programs to be abolished. This happened because of the Covid-19 pandemic which required the Village Government to allocate Village Funds for the fields of disaster management, emergency and urgent villages, namely to handle and cope with the impact of the Covid-19 pandemic, in this case, namely for Village Cash Direct Assistance (BLT-Desa). Based on the description above, the author is interested in conducting more in-depth research on